(untitled) (Journal of Hama University, 2026)
This research aims to identify the role of school principals in using educational aids and laboratory equipment in vocational schools from the teachers’ point of view, and the impact of the variables (school type, school location) on that. In order to achieve the research objectives, the descriptive approach was used and a questionnaire was designed consisting of (20) statements distributed over two axes: administrative tasks and technical tasks. The research sample consisted of (493) male and female teachers in vocational schools in Damascus Governorate. The research concluded that the degree of principals’ implementation of administrative tasks related to the use of educational aids and laboratory equipment in vocational schools is high, and that the degree of principals’ implementation of technical tasks related to the use of educational aids and laboratory equipment in vocational schools is low. The research also concluded that there are statistically significant differences between the average scores of the research sample members’ responses to the questionnaire on the role of school principals in using educational aids and laboratory equipment in vocational schools according to the school type variable in favor of industrial schools, and according to the school location variable in favor of schools located in the city center.